Analisis Pengisian Awal (Impounding) pada Bendungan Raknamo Dengan Model Tangki - Krisnayanti, Denik S; Bolla, Margareth E; Bunganaen, Wilhelmus; Damayanti, Alvine C; Nait, Costandji; Amaral, Bilgardo E.D.N.R (MEDIA KOMUNIKASI TEKNIK SIPIL, 2020)
The impounding of the dam is the step that will be done after construction work on the dam be finished. This study aims to determine a long time and the volume of inflow on Raknamo dam in dry water year, low water year, normal water year and wet water year with tank model. Factors that affected the time of the first impounding of the dam is the amount of rainfall and evapotranspiration that has come in to the catchment area. The total volume of annual inflow Raknamo reservoir obtained in dry water year was in 15,489 million m3, low water year equal to 23,696 million m3, normal water year equal to 32,892 million m3 and wet water year equal to 44,068 million m3. In the calculation of the length of time filling the Raknamo reservoir used the volume of low water year. The accumulation of the volume of every month calculated so that length of time filling the Raknamo reservoir can reach the volume of planned at 14.091 million m3 within three a half months (three months fifteen days).